2014
DOI: 10.4187/respcare.03560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nasal Cannula in Noninvasive Ventilation Using a Lung Simulator

Abstract: BACKGROUND: Nasal noninvasive ventilation (NIV) is a common form of noninvasive respiratory mode used in newborn infants. A next-generation nasal cannula (Neotech RAM cannula) has recently been used to provide nasal NIV. The impact of the Neotech RAM cannula on the delivery of pressure needs to be studied. METHODS: In this ex vivo experimental design, a lung simulator (IngMar ASL 5000, version 3.4) was programmed to model a neonate (ϳ1-3 kg of body weight) with normal-to-moderately affected lungs. We used a Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 12 publications
2
52
2
Order By: Relevance
“…Similar reductions in pressure transduction (up to 60%) have been reported with micro-Preemie, Preemie, and Newborn RAM © cannulas using ventilator-derived CPAP and advanced test lungs [16, 17]. When the RAM © Preemie cannula was tested with NIPPV, transmitted peak inspiratory pressure was 65% of set value, and PEEP was 70% of set value [18]. In contrast, when the BabiPlus © was tested by Poli et al[4] with prongs recommended by the manufacturer, the pressure at the prongs, when set to 6 cm H 2 O, was 6.5 ± 0.01 cm H 2 O.…”
Section: Discussionmentioning
confidence: 68%
“…Similar reductions in pressure transduction (up to 60%) have been reported with micro-Preemie, Preemie, and Newborn RAM © cannulas using ventilator-derived CPAP and advanced test lungs [16, 17]. When the RAM © Preemie cannula was tested with NIPPV, transmitted peak inspiratory pressure was 65% of set value, and PEEP was 70% of set value [18]. In contrast, when the BabiPlus © was tested by Poli et al[4] with prongs recommended by the manufacturer, the pressure at the prongs, when set to 6 cm H 2 O, was 6.5 ± 0.01 cm H 2 O.…”
Section: Discussionmentioning
confidence: 68%
“…However, the risk associated with a tight seal far outweighs the clinical benefit by increasing the propensity for skin breakdown. 12 Iyer et al 18 have shown in an ex vivo experimental design with a lung simulator that the appropriate size interface is imperative: When the cannula size was too small relative to the nasal model diameter, pressure transmission was significantly reduced, resulting in a minimal amount of pressure being applied to the model.…”
Section: Discussionmentioning
confidence: 99%
“…com). We set compliance and resistance values for each model by reviewing previous neonatal bench studies [11][12][13][14][15] as well as clinical studies of lung function tests in preterm infants, [16][17][18][19][20][21] specifically using individual references for each weight group: 0.5 kg, 17,18 1 kg, 19 2 kg, 20 and 4 kg 21 (compliance varying from 0.5 to 5 mL/cm H 2 O/kg; resistance varying from 50 to 350 cm H 2 O/L/s). We calculated resistance values of each endotracheal tube/nasal cannula by using pressure drop across the interface measured with the PTS 2000 (Mallinckrodt, Dublin, Ireland) and average peak flow during invasive ventilation and NIV, and we confirmed that total respiratory resistances were within the range that we estimated for each model ( Table 2).…”
Section: Lung Model and Study Setupmentioning
confidence: 99%
“…In the NIV modes, a nasal cannula (RAM, Neotech, Valencia, California) was used for NIV. 13,29 The nasal cannula was affixed to the model nares using a 22-mm inner diameter plastic adapter (Adapter 962-E, Unomedical, McAllen, Texas). The size of the nasal cannula was selected as follows: "micro preemie" (2.5-mm outer diameter) for 0.5 kg, "preemie" (3.0-mm outer diameter) for 1 kg, "newborn" (3.5-mm outer diameter) for 2 kg, and "infant" (4.0-mm outer diameter) for 4 kg.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%